Evolutionary relationships among the true vipers (Reptilia: Viperidae) inferred from mitochondrial DNA sequences - Lenk, Peter; Wink, Michael (Molecular phylogenetics and evolution, 2001)
Nucleotide sequences of mitochondrial cytochrome b and 16S rRNA genes, totaling 946 bp, were used to reconstruct a molecular phylogeny of 42 species of the subfamily Viperinae representing 12 of the 13 recognized genera. Maximum-parsimony and maximum-likelihood were used as methods for phylogeny reconstruction with and without a posteriori weighting. When representatives of the Causinae were taken as outgroup, five major monophyletic groups were consistently identified: Bitis, Cerastes, Echis, the Atherini (Atheris s.l.), and the Eurasian viperines. Proatheris was affiliated with Atheris, and Adenorhinos clustered within Atheris. The African Bitis consisted of at least three monophyletic groups: (i) the B. gabonica group, (ii) the B. caudalis group, and (iii) the B. cornuta group. B. worthingtoni and B. arietans are not included in any of these lineages. Eurasian viperines could be unambiguously devided into four monophyletic groups: (i) Pseudocerastes and Eristicophis, (ii) European vipers (Vipera s.str.), (iii) Middle East Macrovipera plus Montivipera (Vipera xanthina group), and (iv) North African Macrovipera plus Vipera palaestinae and Daboia russelii. These evolutionary lineages are consistent with historical biogeographical patterns. According to our analyses, the viperines originated in the Oligocene in Africa and successively underwent a first radiation leading to the five basal groups. The radiation might have been driven by the possession of an effective venom apparatus and a foraging startegy (sit-wait-strike) superior in most African biomes and might have been adaptive. The next diversifications led to the Proatheris-Atheris furcation, the basal Bitis splitting, and the emergence of the basal lineages within the Eurasian stock. Thereafter, lineages within Echis, Atheris, and Cerastes evolved. The emergence of three groups within Vipera s.l. might have been forced by the existence of three land masses during the early Miocene in the area of the Paratethys and the Mediterranean Seas. Taxonomic consequences of these findings are discussed.